L'histoire des Montréalaises: un chantier en construction - Baillargeon, Denyse (Vivre en ville. Bruxelles et Montréal aux XIXe et XXe siècles, 2006)
Keywords: Femmes; Histoire

Feminist Historians and Family History in Canada in the 1990's - Bradbury, Bettina (Journal of Family History, 2000)
Number: 3
Keywords: Famille; Féminisme; Histoire; Historiens

Entre la folie d'un seul homme et les violences faites aux femmes: la mémoire collective entourant les événements de la tuerie du 6 décembre 1989 - Blais, Mélissa (Université du Québec à Montréal, 2007)
Keywords: Commémoration; Femmes; Féminisme; École polytechnique

C'était du spectacle!: l'histoire des artistes transsexuelles à Montréal, 1955-1985 - Namaste, Viviane (McGill-Queen's University Press, 2005)
Keywords: Cabarets

Vive la Canadienne! Les représentations de l’identité féminine dans le défilé de la Saint-Jean-Baptiste à Montréal (1924-1961) - Demers, Michel (Université de Sherbrooke, 2001)
Keywords: Femmes; Saint-Jean-Baptiste (fête)

La représentation de l'héroïne dans les romans historiques québécois (1945-1995) ayant comme trame de fond la Nouvelle-France. Les femmes en trois actes: l'épouse, la mère et la veuve - Gingras, Marie-Ève (Université de Sherbrooke, 2008)
Keywords: Femmes; Roman

De colombine à Julien Saint-Michel: le féminisme chez Éva Circé-Côté (1900-1921) - Létourneau, Émilie (Université de Sherbrooke, 2006)
Keywords: Circé-Côté; Éva; Féminisme; Journalistes

Les représentations de la féminité et de la masculinité à travers le thème des rapports amoureux dans la chanson populaire francophone consommée au Québec, 1960-1990 - Ouellette, Myrthô (Université de Sherbrooke, 2006)
Keywords: Chanson; Musique

La représentation féminine dans le contenu publicitaire de La Presse et Le Devoir pendant la Seconde Guerre mondiale (1939-1945): deux visions opposées - Roy, Stéphanie (Université de Sherbrooke, 2007)
Keywords: Devoir (Le); Femmes; Guerre; Presse (La); Publicité

Jeunesse, tu deviendras homme. Les discours identitaires véhiculés au sein de l'Association Catholique de la jeunesse canadienne-française, 1904-1931 - Manseau, Caroline (Université de Sherbrooke, 2006)
Keywords: Association catholique de la jeunesse canadienne-française (ACJC)

J’haïs les féministes. Le 6 décembre 1989 et ses suites - Blais, Mélissa (Les éditions du remue-ménage, 2009)
Keywords: Commémoration; Femmes; Féminisme; École polytechnique

Du silence à l'affirmation: Women Making History in Point St. Charles - Kruzynski, Anna (Université McGill, 2004)
Keywords: Femmes; Pointe-Saint-Charles; Quartiers

Évolution du discours féministe sur "la prostitution" au Québec - Mensah, Maria Nengeh; Laberge, Marie-Claude (Bulletin d'histoire politique, 2006)
issued: 2006-23-00
Keywords: Féminisme; Prostitution

Les femmes patriotes: de la réalité à la fiction - Aubin, Georges (Bulletin d'histoire politique, 2003)
issued: 2003-23-00
Keywords: Femmes; Rébellions

Le maternalisme, une solution féminine à la Crise? La réponse de la Fédération nationale Saint-Jean-Baptiste - Hébert, Karine (Bulletin d'histoire politique, 2001)
issued: 2001-21-00
Keywords: Crise; Fédération nationale Saint-Jean-Baptiste

Contribution de l'Association pour les droits des gai(e)s du Québec (ADGQ) dans l'affirmation des gais au Québec: 1976-1988 - Arsenault, Mathieu (Bulletin d'histoire politique, 2000)
issued: 2000-23-00

Homosexualités: perspectives historico-politiques - Chamberland, Line (Bulletin d'histoire politique, 2008)
issued: 2008-21-00

Les premiers mouvements féministes au Québec, 1893-1940 - Leclerc, Johannie (Université de Sherbrooke, 2008)
Keywords: Féminisme

Étude de cas. Joséphine Marchand-Dandurand: la lecture au féminin - Montreuil, Sophie (Histoire du livre et de l'imprimé au Canada, vol. II (1840-1918), 2005)
Keywords: Femmes; Marchand-Dandurand; Joséphine

"Elles sont partout": Les femmes et la ville en temps d'épidémie. Montréal, 1918-1920 - Fahrni, Magda (Revue d'histoire de l'Amérique française, 2004)
issued: 2004-22-00
Keywords: Bénévolat; Communautés religieuses; Femmes; Infirmières; Épidémies

Carabines, poutchinettes co-eds ou freschettes sont-elles des étudiantes? Les filles à l’Université McGill et à l’Université de Montréal (1900-1960) - Hébert, Karine (Revue d'histoire de l'Amérique française, 2004)
Number: 3
Keywords: Femmes; Université McGill; Université de Montréal; Étudiants

Les femmes et la politique dans les caricatures de Robert La Palme, 1943-1951 - Turgeon, Alexandre (Revue d'histoire de l'Amérique française, 2009)
issued: 2009-23-00/2010-24-00
Keywords: Caricature; Femmes

Permeable Boundaries: Negotiation, Resistance, and Transgression of Street Space in Saint-Henri, Quebec, 1875-1905 - Lord, Kathleen (Urban History Review / Revue d'histoire urbaine, 2005)
issued: 2005-21-00
Keywords: Quartiers; Rues; Saint-Henri

Elsie Reford, une bourgeoise montréalaise et métissienne. Un exemple de spatialisation des sphères privée et publique - Hébert, Karine (Revue d'histoire de l'Amérique française, 2009)
issued: 2009-23-00/2010-24-00
Keywords: Bourgeoisie

A Home away from Home: Defining, Regulating, and Challenging Femininity at the Julia Drummond Residence in Montreal, 1920–1971 - Kirkland, Elizabeth (Urban History Review / Revue d'histoire urbaine, 2006)
Number: 2
Keywords: Femmes; Logement

"Bonifier le capital humain". Le genre dans le discours médical et religieux sur les sports au Québec, 1920-1950 - Detellier, Élise (Revue d'histoire de l'Amérique française, 2009)
issued: 2009-24-00/2009-21-00

Autorité, genre et expertise: le cas de l’assistance catholique à Montréal - Bourbeau, Amélie (Revue d'histoire de l'Amérique française, 2009)
issued: 2009-23-00/2010-24-00
Keywords: Federation of Catholic Charities (FCC); Fédération des œuvres de charités canadiennes-françaises (FOCCF)

Louise Paradis: une femme à la tête du domaine Saint-Gabriel des Sulpiciens - Blondin, Yves (Les cahiers d'histoire de Pointe-Saint-Charles, 2009)
Keywords: Baux à ferme; Communautés religieuses; Famille; Femmes; Saint-Gabriel (ferme); Sulpiciens

William Notman’s Portrait Photographs of the Wealthy English-speaking Girls of Montreal: Representations of Informal Female Education in Relation to John Ruskin’s “Of Queens’ Gardens” and Writings by and for Canadians from the 1850s to 1890s - Lerner, Loren Ruth (Revue d'histoire de l'éducation / Historical Studies in Education, 2009)
issued: 2009-23-00
Keywords: Bourgeoisie; Femmes

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens

Visualising the History of Women at Eaton's, 1869 to 1976 - O'Donnell, Lorraine Frances (Université McGill, 2002)
This thesis examines the place of female customers and employees at the T. Eaton Company of Canada between 1869 and 1976. The central argument is that the word "witness" conveys well the nature of their place in this, one of the most important retail firms in Canadian history. Women were witnesses for the Eaton's and its development. They attested to and consolidated the company by collectively supporting it in huge numbers, whether as customers or personnel. Women were also key eyewitnesses of Eaton's, of its merchandise and marketing, its stores and catalogues. As the word "witness" suggests, visuality was central to women's central place. Women bought into the Eaton's buying and selling strategies that privileged appearances, and the company assumed and fostered this visually-centered role, helping to construct it and encouraging women to adopt it. The Introduction to the thesis reviews the substantial literature on the company's history. The main body of the thesis is divided in two. Part I examines the company's foreign activities and the role of women therein. Following a description of the firm's foreign buying system is an examination of three of its main regions: Japan, Europe and the U.S.A. The closer the region was to Canada, the more familiar it was to Eaton's, the more female Eatonians were employed there, and the more these women were able carve out a niche for themselves as expert witnesses like fashion buyers or fashion reporters. Part II discusses the place of women in the company's activities within Canada. First, it outlines the history of and tensions between the company's two main retail sites: stores and catalogues. While run by men, these sites were "spectacles of women" including salesclerks, mannequins and customers. Examples considered in depth are Eaton's catalogue covers and store displays for foreign goods and places. They privileged female imagery, a strategy meant to add value both to the merchandise and the (incomplet)
Keywords: Eaton; Femmes; Magasins

"S'unir pour être plus fort": le Conseil des femmes membres de la Chambre de commerce du district de Montréal, 1956-1971 - Detellier, Élise (Université de Montréal, 2004)
Keywords: Chambre de commerce; Femmes

Les Yvettes comme l’expression d’un féminisme fédéraliste au Québec - Godin, Stéphanie (Université du Québec à Montréal, 2003)
Keywords: Féminisme

Manly Smokes: Tobacco Consumption and the Construction of Identities in Industrial Montreal, 1888-1914 - Rudy, Robert Jarrett (Université McGill, 2001)
This dissertation explores the cultural practice of smoking and its connection to social relations from the beginning of cigarette mass production in Montreal in 1888 to the First World War. It uncovers the norms of smoking etiquette and taste, their roots in gender, class and race relations and their use in reproducing these power relationships. It argues that these prescriptions reflected and served to legitimize beliefs about inclusion, exclusion and hierarchy that were at the core of nineteenth century liberalism. Liberal ideals of self-control and rationality structured the ritual of smoking: from the purchase of tobacco; to who was to smoke; to how one was supposed to smoke; to where one smoked. These prescriptions served to normalize the exclusion of women from the definition of the liberal individual and to justify the subordination of the poor and cultural minorities. Furthermore, even while these prescriptions were at their height, an emergent group of beliefs began to recast notions of respectable smoking around new ideals of speed and ungendered universality. This challenge was not only part of the transition from bourgeois to mass consumption, it was the roots of a transformation of the liberal order in the years previous to the First World War.
Keywords: Tabac

Fréquentations et mariage, les représentations de jeunes québécoises à travers l'étude d'un courrier du coeur (1958-1968) - Sénéchal, Johanne (Université Laval, 2006)
Keywords: Bertrand; Janette; Femmes; Mariage

La question du travail domestique au début du XXe siècle au Québec: un enjeu à la Fédération nationale Saint-Jean-Baptiste, 1900-1927 - Charron, Catherine (Université Laval, 2007)
Keywords: Fédération nationale Saint-Jean-Baptiste; Travail

"It's Funny the Things You Remember": Memories of Gendered Childhood in Montreal during the Great Depression - Rebelo, Nancy Moniz (Université Concordia, 2007)
Keywords: Crise; Enfants

Under Reconstruction: the Family and the Public in Postwar Montréal, 1944-1949 - Fahrni, Magda (Université York, 2001)
Keywords: Famille; Guerre

Hier ne meurt jamais. Vision et désillusions d'une quête identitaire féminine au Québec. La Bonne Parole, organe de la Fédération nationale Saint-Jean-Baptiste, 1913-1958 - Dornic, Isabelle (Université Laval, 2004)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste

L’idéal maternel: discours, représentation et célébration des mères québécoises à l’occasion de la fête des mères, 1940-1980 - Marando, Nancy (Université de Montréal, 2006)
Keywords: Enfants; Famille; Femmes; Montreal Star; Presse (La)

Vers l’avenir. Québec Women’s Politics Between 1945 and 1967: Feminist, Maternalist and Nationalist Links - Gosselin, Cheryl A. (Université de Montréal, 2002)
Keywords: Femmes; Féminisme; Nationalisme

Perspectives féminines sur les hommes et le couple. Châtelaine, 1960-1975 - Malo, Isabelle (Université de Montréal, 2005)
Keywords: Femmes

Les règles du jeu de la séduction dans les manuels de savoir-vivre québécois (1863-1917): investir le monde du sentiment et de l’intimité masculine - Roy, Sonya (Université de Montréal, 2006)
Keywords: Bourgeoisie; Mariage

Days and Nights: Class, Gender and Society on Notre-Dame Street in Saint-Henri, 1875-1905 - Lord, Kathleen (Université McGill, 2000)
Keywords: Quartiers; Rues; Saint-Henri

Commercialisation des produits de beauté, pratiques esthétiques et représentations du corps de la femme à Montréal, 1870-1915 - Chartrand, Mélanie (Université de Montréal, 2004)
Keywords: Femmes; Publicité

Faith, Family, Female Education and Friendship: Retelling Louise Amelia Monk's Adolescence in Bourgeois Montreal, 1867-1871 - Brettler Vandervort, Jessica L. (Université Concordia, 2003)
Keywords: Bourgeoisie; Femmes

Parrots, picnics and psychic phenomena: The feminism, nationalism and social reform of Eva Circé-Côté in Le Monde Ouvrier's Montreal, 1900-1940 - MacLean, Jenne (Queen's University, 2000)
Keywords: Circé-Côté; Éva; Féminisme; Journalistes; Monde ouvrier (Le); Nationalisme

La construction du père québécois: le discours du mouvement familial et l’expérience des pères, 1945-1965 - Duhaime, Vincent (Université de Montréal, 2000)
Keywords: Famille

Un discours masculin sur la société: la publicité dans les quotidiens québécois des années 1920 aux années 1960 - Couvrette, Sébastien (Université du Québec à Montréal, 2009)
Keywords: Devoir (Le); Montreal Star; Presse (La); Publicité

Jeunes femmes et loisirs commerciaux durant les années folles (1919-1929): Étude des discours ecclésiastiques et journalistiques - Comtois, Patricia (Université du Québec à Montréal, 2007)
Keywords: Femmes; Patin; Ski

"Les femmes accélèrent la machine de guerre": le travail des femmes durant la Seconde Guerre mondiale dans Le Monde ouvrier - Detellier, Élise (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2003)
issued: 2003-23-00
Keywords: Confédération des travailleurs catholiques du Canada (C.T.C.C.); Conseil des métiers et du travail de Montréal; Femmes; Fédération des travailleurs et travailleuses du Québec (FTQ); Guerre

Le Montreal Council of Women / Conseil des Femmes de Montréal, de 1940 à 1967, à travers les questions de planification urbaine, d'immigration et des femmes dans le monde du travail - Hilairet, Sabine (Université d'Angers, 2003)
Keywords: Femmes; Féminisme; Montreal Local Council of Women; Travail

Bending the Rules: The Montreal Branch of the Woman's Art Association of Canada, 1894-1900 - Haskins, Victoria (Université Concordia, 2005)
Keywords: Art association; Femmes